Constitutive Expression of the AP-1 Transcription Factors c-jun, junD, junB, and c-fos and the Marginal Zone B-Cell Transcription Factor Notch2 in Splenic Marginal Zone Lymphoma - Trøen, Gunhild (American Society for Investigative Pathology, 2004)
Splenic marginal zone lymphoma (SMZL) is a lymphoma type of putative marginal zone B-cell origin. No specific genetic alterations have yet been demonstrated in SMZL. Clinically, SMZL is a low-grade B-cell non-Hodgkin lymphoma. However, the presence of p53 mutation, 7q22–7q32 deletion or the absence of somatic hypermutations of immunoglobulin genes has been correlated with a worse prognosis. In this study, we analyzed genome-wide gene expression of 24 cases of SMZL using the microarray technique. The AP-1 transcription factors c-jun, junD, junB, and c-fos as well as Notch2 were found to be specifically up-regulated. These data were confirmed by real-time PCR and immunohistochemical staining of tissue sections. The absence of concordant high expression of the MAP kinases, the signaling cascade leading to AP-1 up-regulation, suggests autoregulation of the AP-1 transcription factors and an important role in SMZL oncogenesis. High expression of Notch2, a transcription factor that induces marginal zone B-cell differentiation, is highly suggestive for a marginal zone B-cell origin of SMZL. In addition, SMZL with the 7q deletion showed high expression of TGF-β1 and low expression of the DNA helicase XPB, a crucial part of the nucleotide excision repair complex, possibly explaining the more aggressive clinical course of those cases.